The ventral capsule and ventral striatum—Stereotactic targets for the management of treatment-resistant depression. A systematic literature review - Michał Sobstyl; Marek Prokopienko; Tadeusz Pietras (Frontiers in Psychiatry, 2023)
BackgroundDeep brain stimulation (DBS) is still an experimental treatment modality for psychiatric disorders including treatment-resistant depression (TRD). There is preliminary evidence that stimulation of brain reward circuit structures including the ventral striatum (VS) may exert an antidepressant effect. The main nucleus of the reward circuit is the nucleus accumbens (NAc). The NAc is a major structure of VS that plays a critical role in reward-seeking behavior, motivation, and addiction.AimsThis study aimed to review the current studies including randomized clinical trials, open-label trials, and case reports of NAc/VS and VC DBS for TRD in humans.MethodThe literature was reviewed using a medical database—Medical Literature, Analysis, and Retrieval System Online (MEDLINE) on NAc/VS or VC DBS in TRD. The identified studies were assessed based on the patient's characteristics, clinical outcomes, and adverse events related to DBS as well as the stereotactic technique used to guide the implantation of DBS electrodes. The inclusion and exclusion criteria of DBS for TRD were presented and discussed.ResultsThe searched literature revealed one case report, three open-label studies (OLS), one multicenter open-label study (mOLS), and two randomized clinical trials (RCTs). There were three additional studies reporting the clinical outcomes in the long term in TRD patients included in the two mentioned RCTs. The total number of patients with TRD treated by NAc/VS or VC is estimated to be 85 individuals worldwide. The response rate to DBS defined as a 50% reduction of postoperative Montgomery-Asberg Depression Rating Scale (MADRS) scores was achieved in 39.8% of the operated patients (range, 23–53%). The remission defined as MADRS scores of < 10 was found in 17.8% after DBS (range, 0–40%). The mean follow-up was 19.7 months (range 3.7–24 months).ConclusionThe current results of NAc/VS and VC DBS are still limited by a relatively small number of patients treated worldwide. Nevertheless, the results suggest that NAc/VS and VC can be regarded as promising and efficacious targets for DBS, taking into account the response and remission rates among TRD patients with no other treatment option. The adverse events of NAc/VS and VC DBS are reversible due to the adjustment of stimulation parameters. The most common adverse events were hypomanic/manic states, suicidal thoughts/attempts, and suicides. Patients with TRD after NAc/VS and VC DBS should be strictly followed to prevent or diminish these stimulation-induced adverse events.